The importance of surface composition and wettability on the dissolution performance of high drug loading amorphous dispersion formulations - Hiew, Tze Ning; Solomos, Marina A.; Kafle, Prapti; Polyzois, Hector; Zemlyanov, Dmitry Y.; Punia, Ashish; Smith, Daniel; Schenck, Luke; Taylor, Lynne S. (Journal of pharmaceutical sciences, 2025)
One of the limitations with an amorphous solid dispersion (ASD) formulation strategy is low drug loading. Hydrophobic drugs have poor wettability and require a substantial amount of polymer to stabilize the amorphous drug and facilitate release. Using grazoprevir and hypromellose acetate succinate as model drug and polymer, respectively, the interplay between particle surface composition, particle wettability, and release performance was investigated. A hierarchical particle approach was used where the surfaces of high drug loading ASDs generated by either solvent evaporation or co-precipitation were further modified with a secondary excipient (i.e., polymer or wetting agent). The surface-modified particles were characterized for drug release, wettability, morphology, and surface composition using two-stage dissolution studies, contact angle measurements, scanning electron microscopy, and X-ray photoelectron spectroscopy, respectively. Despite surface modification with hydrophilic polymers, the hierarchical particles did not consistently exhibit good release performance. Contact angle measurements showed that the secondary excipient had a profound impact on particle wettability. Particles with good wettability showed improved drug release relative to particles that did not wet well, even with similar drug loadings. These observations underscore the intricate interplay between particle wettability and performance in amorphous dispersion formulations and illustrate a promising hierarchical particle approach to formulate high drug loading amorphous dispersions with improved dissolution performance. [Display omitted]